Wine yeast species show strong inter- and intra-specific variability in their sensitivity to ultraviolet radiation. (December 2021) - Pilard, Etienne; Harrouard, Jules; Miot-Sertier, Cécile; Marullo, Philippe; Albertin, Warren; Ghidossi, Rémy
Abstract: While the trend in winemaking is toward reducing the inputs and especially sulphites utilization, emerging technologies for the preservation of wine is a relevant topic for the industry. Amongst yeast spoilage in wine, Brettanomyces bruxellensis is undoubtedly the most feared. In this study, UV-C treatment is investigated. This non-thermal technique is widely used for food preservation. A first approach was conducted using a drop-platted system to compare the sensitivity of various strains to UV-C surface treatment. 147 strains distributed amongst fourteen yeast species related to wine environment were assessed for six UV-C doses. An important variability in UV-C response was observed at the interspecific level. Interestingly, cellar resident species, which are mainly associated with wine spoilage, shows higher sensitivity to UV-C than vineyard-resident species. A focus on B. bruxellensis species with 104 screened strains highlighted an important effect of the UV-C, with intra-specific variation. This intra-specific variation was confirmed on 6 strains in liquid red wine by using a home-made pilot. 6624 J.L −1 was enough for a reduction of 5 log10 of magnitude for 5 upon 6 strains. These results highlight the potential of UV-C utilization against wine yeast spoiler at cellar scale. Highlights: Strong interspecific variation was observed to UV-C radiation for the main yeast species encountered in winemaking. Sensitivity was associated with the ecological niche of the yeast species (cellar resident species being more sensitive to UV-C treatment than the vineyard-resident ones). B. bruxellensis was highly sensitive to UV-C compared to others species.